Rule of Law, Control of Corruption and CO2 Emissions in Pakistan - Mahmood, Haider; Hassan, Shafiqul; Tanveer, Muhammad; Furqan, Maham (International Journal of Energy Economics and Policy, 2022)
The rule of law and control of corruption would play an effective role in managing CO2 emissions in Pakistan. The present research has explored this issue in Pakistan controlling economic growth during 1996-2019. Further, the unit root and cointegration tests are used. We found the long and short-run relationships in the model. Economic growth has a positive effect on CO2 emissions. The rule of law could not impact in the long run and negatively impacts in the short run. Hence, improving law and order conditions would reduce CO2 emissions in the short run, and further improvements in the rule of law could have pleasant long-run environmental effects. The control of corruption has a positive impact on CO2 emissions in the long run. However, the short-run effects of control of corruption with first and second lags are found negative.